THE RELATIONSHIP OF DENTAL BRUSHING KNOWLEDGE WITH THE STATUS OF DENTAL AND MOUTH HYGIENE IN THE VIII CLASS ADOLESCENT OF SMPN 1 DARUL IMARAH ACEH BESAR, 2022 - Andriani; Ulfasari , Putri (Jurusan Kesehatan Gigi Poltekkes Kemenkes Aceh, 2022)
The maintenance of dental and oral health is often neglected by teenagers. Many bad habits of teenagers that can cause damage to the teeth and mouth, these bad habits include the habit of consuming sweet foods, drinking habits - sweet drinks and lazy habits of brushing your teeth at night. The results of the examination that the author conducted on 15 grade VIII students at SMPN 1 Darul Imarah, the average dental and oral hygiene was 3.3 with a poor category level. The results of interviews with 11 out of 15 students still did not know how to brush their teeth properly and correctly. The purpose of this study was to determine the relationship between knowledge of brushing teeth and the status of dental and oral hygiene in Class VIII Adolescents of SMPN 1 Darul Imarah Aceh Besar in 2022.This research is analytical with a cross sectional design, conducted at SMPN 1 Darul Imarah Aceh Besar District on 19-22 February 2022. The population in this study was 210 people. The sample in this study used a random sampling technique with a sample of 70 adolescents aged 13-14 years. Bivariate analysis looked at the relationship between knowledge of brushing teeth and oral hygiene status using the statistical test of 0.05.The results showed that the knowledge of brushing teeth with the most dental and oral hygiene status was in the moderate category as many as 20 people (28.6%), the knowledge of brushing teeth was not good with the most dental and oral hygiene status in the poor category as many as 23 people (32, 8%). It can be concluded that there is a relationship between knowledge of brushing teeth with dental and oral hygiene status in adolescents with a P Value: 0.01, it is recommended for adolescents to be more active in seeking information on social media about knowledge or maintenance of dental health such as brushing teeth properly and correctly so that avoid poor dental and oral hygiene status.